Jamming recognition method based on the polarisation scattering characteristics of chaff clouds. Issue 11 (10th October 2017) - Liu, Yemin; Xing, Shiqi; Li, Yongzhen; Hou, Dong; Wang, Xuesong
Abstract : Chaff is composed of small and thin pieces of glass fibres plated with aluminium or silver and is dispersed in the air like a cloud from air fighters or warships. The length of a chaff fibre is generally much smaller than the radar resolution and its orientation is random in chaff clouds. Therefore, chaff clouds can be viewed as anisotropic needle‐like particles. For such kind of target, according to the polarimetric decomposition theorem, identifying the dominant physical scattering mechanism is the polarimetric scattering parameter, which is a roll‐invariant parameter. As a result, this parameter is introduced to investigate the scattering characteristics of chaff clouds here. Theoretical analysis shows that this parameter of chaff clouds with three typical orientation distributions varies between 45 ∘ and 49 ∘ . Moreover, when the azimuth angles of chaff clouds meet the uniform distribution, the correlation of chaff clouds between the co‐ and cross‐polarised channels vanishes. To this end, the polarisation scattering characteristics of chaff clouds mentioned above are validated by numerical simulation, and a study is also carried out to compare the chaff clouds with other targets, which confirms the feasibility and real‐time of chaff jamming recognition by support vector machine classification method.